Development Of Real-Time IoT-Based Environmental Monitoring System For Air Quality - Ng, Wei Jian (Universiti Sains Malaysia, 2018)
Nowadays, modernization has improved the lifestyle of human. However, the crisis regarding air pollution has been increased which brings a lot of problems to human health and environment such as acid rain, global warming and the deterioration of the ozone layer. The emission of carbon monoxide from the vehicle on road makes people feel dizzy and tired and gives them headaches Thus, this project proposes the development of real-time Internet of Things (IoT)-based environmental monitoring system for air quality. This monitoring system integrates three sub-systems which consists of environmental air quality sensing system, smart alerting system and real-time monitoring system. The environmental air quality sensing system utilizes a gas sensor to determine the concentration of carbon monoxide, liquefied petroleum gas (LPG) and smoke and a humidity and temperature sensor to measure the temperature and humidity of environment. Then, the smart alerting system warns the surrounding people by activating the alarm and displaying the warning message when the air quality of environment is poor. In addition, the real-time monitoring system is used to observe the real-time measurement of air quality via an Android application “AirProp” for many users at the same time. Moreover, the effects of factors such as time and traffic condition on the temperature, humidity and concentration of pollutant gases are also investigated. At the end of this research, it is found that the alarm system is triggered when the concentration of carbon monoxide exceeds 50 ppm. Besides that, the Android application enables users to monitor the real-time measurement of environmental air quality as well as review the past data on a specific date via Wi-Fi. These data can be analyzed and leveraged by governments and researchers to mitigate air pollution. Heavier traffic during peak hour periods is one of the greatest contributing factors in higher concentrations of air pollutants. The highest average concentration of carbon monoxide, LPG and smoke is obtained at Kulim Hi-Tech Park in the evening. The Air Quality Index (AQI) that calculated based on the concentration of carbon monoxide is 50. The air quality is considered satisfactory and causes no risk on healthy of human. In conclusion, the proposed system has been successfully developed with the technology of IoT.